The Role of Weather on Investors' Monday Irrationality: Insights from Malaysia - Rayenda Brahmana; Chee Wooi Hooy; Zamri Ahmad (Contemporary Economics, 2014)
Evidence supporting the weekend effect, also known as Monday Irrationality, has shown that conventional finance is unable to follow a rational behavior assumption. Many scholars have proposed a behavioral approach to explain this phenomenon; however, few studies have investigated this effect empirically. Interestingly, literature on weather patterns and the preliminary results of our study have identified a particular weather cycle that occurs on Mondays, when the temperature in Malaysia is higher compared with other days. Therefore, this paper aims to investigate the role of weather on investors' Monday irrationality. By analyzing the market index and size-based portfolio formation model from 1999 to 2010, this research study found that the weather influenced investors' mood, causing anomalous conditions in the market. Our findings conclude that the mood of investors plays an important role on investment decisions and the resulting Monday irrationality of investors.
Keywords: D03; G12; G14; 330; weather; monday irrationality; psychological finance; malaysian stock market